Sr. Frango da Guia : success or failure in Brazil - Costa, Mauro, (SAGE Knowledge. Cases., 2013)
The sun was slowly sinking behind the horizon as Manuel Costa waited for his flight from S?o Paulo back to Portugal. He was feeling restless. A tough decision stood before him and he would have to make up his mind soon.It was 2004 and Costa had been struggling with his Brazilian restaurants for some two years. At first expanding his successful chicken restaurants Sr. Frango da Guia (SFG) to Brazil had seemed like an easy enterprise. After all, Brazil and Portugal shared a common language and had historical ties. Unfortunately, problems soon started to crop up. The Brazilian restaurants performed below expectation and several thefts by the employees had been reported. It was also difficult for Costa to keep a tight control on the businesses in Brazil due to the large distance separating him, in Lisbon, from them. To make matters worse, the Brazilian real was rapidly losing in value.Costa had to come to a decision about his Brazilian restaurants. Should he keep his restaurants in Brazil open, or should he close them down? If he did decide to keep them open he would need to make some drastic changes to ensure the profitability of the restaurants. The question was what these changes should be.